The Rediscovery and Resurrection of Bunk Johnson – a Grounded Theory Approach: - Richard Ekins (Grounded Theory Review: An International Journal)
This paper was written in the beginning phase of my transitioning from grounded theory sociologist (Ekins, 1997)1 to grounded theory musicologist (Ekins,2010)2. In particular, it provides preliminary data for a grounded theory of "managing authenticity", the core category/ basic social process (Glaser, 1978) that has emerged from my ongoing grounded theory work in jazz historiography. It was written whilst I was redentialising (Glaser, 2010) my transition to popular music studies and popular musicology. In consequence, it incorporates many aspects that are inimical to classic grounded theory. As with so much of Straussian and so-called constructivist grounded theory (Bryant and Charmaz, 2007), it roots itself in G.H. Mead and a social constructivist symbolic interactionism inter alia, a legitimising (authenticating) strategy. Moreover, as is typical of this mode of conceptualising, the paper fills the void of inadequate classic grounded theorising with less conceptual theorising and more conceptual description. Nevertheless, the article does introduce a number of categories that "fit and work" , and have conceptual grab (Glaser,1978; Glaser, 1992). In particular, in terms of my own continuing credentialising as a classic grounded theorist, it sets forth important categories to be integrated into my ongoing work on managing authenticity in New Orleans revivalist jazz, namely, trailblazing, mythologizing, debunking, and marginalising, in the context of rediscivering and resurrecting of a jazz pioneer. More specifically, the paper is offered to classic grounded theorists as a contribution to preliminary generic social process analysis in the substantive area of jazz historiography.